Учет коммуникативных потребностей как условие эффективного обучения профессионально ориентированной диалогической речи иностранных студентов-медиков - Рагрина, Ж. М.; Рагріна, Жанна Михайлівна; Ragrina, Z. M. (My University, 2015)
В статье раскрываются основные особенности профессионально ориентированной диалогической речи медиков. Обосновывается необходимость учета коммуникативных потребностей для эффективного обучения профессионально ориентированной диалогической речи иностранных студентов медицинских специальностей. У статті розкриваються основні особливості професійно орієнтованої діалогічної мови медиків. Обґрунтовується необхідність врахування комунікативних потреб для ефективного навчання професійно орієнтованої діалогічної мови іноземних студентів медичних спеціальностей. Professionally oriented learning a foreign language now recognized as a priority in the renewal of education. By profession oriented learning refers learning based on the needs of students in learning a foreign language, dictated by the characteristics of their future profession or specialty. It involves a combination of mastering professional-oriented foreign language with the development of personal qualities of students, knowledge of the culture of the country of the studied language and the acquisition of specific skills, based on the professional and linguistic knowledge. Professionally oriented learning a foreign language in not language high schools includes components such as learning a foreign language as a means of mastering the profession and as a means of professional communication. The article describes the main features of the professional oriented dialogue speech physicians. The research is devoted to the explanation of necessity teaching professionally oriented dialogic speech with understanding the communicative needs of foreign medical students.
Врахування комунікативних потреб як умова ефективного навчання професійно орієнтованої діалогічної мови іноземних студентів-медиків.
Analysis of communicative needs for effective teaching professionally oriented dialogic speech of foreign medical students.
Keywords: коммуникативные потребности; диалог; диалогическая речь; профессионально ориентированное общение; комунікативні потреби; діалог; діалогічне мовлення; професіонально орієнтоване спілкування; communicative needs; dialogue; dialogue speech; professionally oriented communication